A new approach to the preeclampsia puzzle; MicroRNA-326 in CD4+ lymphocytes might be as a potential suspect. (June 2021) - Zolfaghari, Mohammad Ali; Motavalli, Roza; Soltani-Zangbar, Mohammad Sadegh; Parhizkar, Forough; Danaii, Shahla; Aghebati-Maleki, Leili; Noori, Mohammad; Dolati, Sanam; Ahmadi, Majid; Samadi Kafil, Hossein; Jadidi-Niaragh, Farhad; Ahmadian Heris, Javad; et al.
Highlights: The molecular mechanisms of preeclampsia have not been fully understood and multifactorial processes are involved in PE pathogenesis. The level of miRNA-326 increases in preeclamptic pregnancy, especially in Th17 and CD4 + T cells. The CD4 + T-cell subset could be an extra source of antiangiogenic factors for the maintenance of this hypertension disorder. Abstract: Background: Alongside many complications in understanding the etiology of Preeclampsia (PE), several determinants, such as the imbalanced proportion of anti-angiogenic/proangiogenic T-cell subsets, especially CD4 + (Th17/Treg), as well as alterations in the expression profile of related cytokines, miRNAs, and transcription factors might have been implicated in PE pathogenesis. Material and method: After sample collection and preparation, CD4 + cells were isolated from PE and non-PE pregnant woman and were cultured. Furthermore, analysis such as flow cytometry, real-time PCR, western blotting, and ELISA were performed to assess determinants related to PE manifestation, including sFlt-1, sEng, STAT-3, RORγt, SMAD-7, Foxp3, IL-17, IL-22, Ets-1, and miRNA-326 . Results: Our results showed that the miRNA-326 expression level increased in CD4 + Cells and Th17 in PE patients which downregulated Ets-1 expression that acts as a negative control for Th17 development. Furthermore, we showed that the number and expression level of Th17 s and transcription factor ROR γ t escalated, respectively. While Treg and its related transcription factor (Foxp3) demonstrated a decrease. Flow cytometry analysis illustrated that the Th17/Treg ratio increased in PE. Additionally, we demonstrated that expression and concentration levels of cytokines (IL-17 and IL22) and anti-angiogenic molecules (sEng and sFlt-1) soared in isolated CD4 + cells from PE patients, which could be correlated with PE pathogenicity. Conclusion: In conclusion, we comprehensively evaluated immunological factors and molecules involved in PE manifestation. Interestingly, the CD4 + T-cell subset could be an extra source of antiangiogenic factors for the maintenance of this hypertension disorder.